Nutritional management of the critically ill obese patient - Mat Nor, Mohd Basri; Ibrahim, Noor Airini; Abdullah, Fa’iza (International Islamic University Malaysia, 2018)
Purpose of review: The prevalence of obesity in Malaysia has increased four folds over the past two decades. Epidemiologic studies suggest that there are increased numbers of overweight and obese patients admitted to the intensive care unit (ICU). Increased morbidity and mortality along with longer duration of ICU stay and time on mechanical ventilator have been shown to be associated with this particular body habitus. This review will discuss the recent findings and evidence-based approaches to provide nutrition therapy for this ICU population. Recent findings: Nutrition therapy plays a vital role in improving their outcome; however, clinicians need knowledge of certain obstacles that are unique to obese patients. Nutrition assessment should be comprehensive, because the presence of malnutrition is always underestimated. The increased basal insulin level suppresses lipid mobilisation but increases protein breakdown in obesity, thus leading to protein malnutrition. Large variations in body composition among the obese make estimation of caloric requirements very difficult. There is no consensus as to which predictive equation is most suitable, leading to the recommendation to perform indirect calorimetry when available. A more balanced nitrogen profile has been shown following a high-protein, hypocaloric feeding regimen as compared to a eucaloric one while also demonstrating better outcomes. Summary: Future studies should focus on finding a method to determine appropriate energy requirements and validate the benefits of a high-protein, hypocaloric feeding regimen in critically ill obese patients.